2003
DOI: 10.1128/aem.69.6.3393-3398.2003
|View full text |Cite
|
Sign up to set email alerts
|

Giardia Cysts in Wastewater Treatment Plants in Italy

Abstract: Reductions in annual rainfall in some regions and increased human consumption have caused a shortage of water resources at the global level. The recycling of treated wastewaters has been suggested for certain domestic, industrial, and agricultural activities. The importance of microbiological and parasitological criteria for recycled water has been repeatedly emphasized. Among water-borne pathogens, protozoa of the genera Giardia and Cryptosporidium are known to be highly resistant to water treatment procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
75
2
13

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 38 publications
9
75
2
13
Order By: Relevance
“…Failure to obtain positive PCR results from wastewater samples containing Cryptosporidium oocysts has also been reported by others (1). It is unknown whether this was due to insufficient DNA or inhibition of the PCR.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Failure to obtain positive PCR results from wastewater samples containing Cryptosporidium oocysts has also been reported by others (1). It is unknown whether this was due to insufficient DNA or inhibition of the PCR.…”
Section: Discussionmentioning
confidence: 87%
“…Giardia duodenalis cysts has been used in a variety of studies to further elucidate aspects of the epidemiology, both conventional and molecular, of these parasites in particular populations or geographic regions (1,20). Additionally, such analyses can be used as an indirect method of assessing the occurrence of these infections in human populations (12,17,18).…”
Section: Analysis Of Sewage Influent For Cryptosporidium Oocysts Andmentioning
confidence: 99%
“…Molecular studies have shown that the majority of human cases are caused by C. hominis and C. parvum (Anonymous 2000, McLauchlin et al 2000. The oocysts of this parasite can be readily found in sludge, raw sewage, sewage effluents, drinking water and recreational waters (Bukhari et al 1997, Fayer et al 2000, Robertson et al 2000, Caccib et al 2003, and may represent a public health risk in developed and developing countries (LeChevalier et al 1991a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Human sewage has been considered a source of Giardia cyst contamination in water. In Canada and Italy, a high prevalence (73 to 100%) of Giardia cysts was reported in raw sewage samples (4,14,34). The public health importance and contamination sources of Giardia cysts found in water, however, are largely unclear, because very few studies have been carried out to genetically characterize the Giardia cysts in water.…”
mentioning
confidence: 99%
“…In recent years, several attempts have been made to detect and differentiate Giardia spp. in environmental samples by using PCR techniques (4,31,34). The distribution of Giardia spp.…”
mentioning
confidence: 99%